2017
DOI: 10.1515/jomb-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Syrgical Trauma on Nitric Oxide and Nitrotyrosine Serum Levels in Patients Undergoing Laparoscopic or Conventional Cholecystectomy

Abstract: SummaryBackgroundOxidative stress represents tissue damage caused by reactive forms of oxygen and nitrogen due to the inability of antioxidant mechanisms to reduce reactive forms into more stable ones. The aim of the study was to evaluate the influence of surgical trauma on nitric oxide (NO) and nitrotyrosine (NT) values in patients undergoing conventional and laparoscopic cholecystectomy.MethodsA prospective study included sixty patients from the Department of Emergency Surgery, Clinical Centre of Serbia who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…However, IL-6 growth during open cholecystectomy was greater compared to laparoscopic cholecystectomy (62.51-fold vs. 3.19-fold). Our results are in line with other studies indicating increased inflammatory response in open surgery in comparison to the equivalent laparoscopic one [ 19 22 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, IL-6 growth during open cholecystectomy was greater compared to laparoscopic cholecystectomy (62.51-fold vs. 3.19-fold). Our results are in line with other studies indicating increased inflammatory response in open surgery in comparison to the equivalent laparoscopic one [ 19 22 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies show that levels of circulating plasma proinflammatory cytokines, including IL-6, are related to the extent and severity of surgical procedure [ 18 22 ]. IL-6 concentration was mostly measured in plasma or serum [ 18 20 ]; rarely, it was assessed in peritoneum [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…White blood cells subtypes follow various inflammatory reactions of the body. Recently, neutrophilia and relative lymphopenia were proposed as predictors of mortality in patients with heart failure, but could also be successful indicators in the determination between simple and severe acute cholecystitis (1, 13, 14). NLR represents a combination of two markers where neutrophils are the active non-inflammatory mediator initiating the first line of defense, where as lymphocytes represent the regulatory or protective component of inflammation (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Previously proposed white blood cell count (WBC) and CRP as indicators of severity of acute cholecystitis are insufficient because in some patients those parameters can be within a normal reference range. In some studies, it was suggested that raised NLR can be associated with severity of cholecystitis and prolonged hospitalization after surgery (1, 2, 12, 13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical trauma elicits marked changes in cytokine levels, impaired metabolic response and increase of acute phases proteins (4). Inflammatory response of the body in perioperative period is a protective mechanism which promotes better recovery, while excessive inflammatory response in severe tissue injury could contribute to development of complications and impaired wound healing (5). During the adaptation on surgical stress negative nitrogen balance provokes peripheral fat utilization and leads to increase in glucose production.…”
Section: Introductionmentioning
confidence: 99%